Deaf student’s inclusion in the context of professional and technological education: results of a diagnostic research (Research, Society and Development, 2022)
In December 2016, Law No. 13,409 was published, which provided for the reservation of vacancies for people with disabilities in higher education and high school technical courses at federal educational institutions (Ifes). Since then, Ifes have faced the challenge of including students with different specific educational needs in their school spaces. This article intends to investigate the inclusion of deaf students according to teacher’s perspective from an integrated high school technical course at the Federal Institute of Education, Science and Technology of Alagoas (Ifal). Therefore, the qualitative methodology was used, based on action research, through the application of a semi-structured questionnaire. The results pointed out blanks in the inclusion process for deaf students, such as the lack of professional translators and interpreters of Libras, the lack of knowledge about Deaf Culture in pedagogical planning and the need for continuing education for teachers focused on school inclusion. Finally, teachers also indicated possible actions to minimize such difficulties, so that teaching practice is, in fact, based on the principles that make up Inclusive Education.